2006
DOI: 10.1093/aje/kwj282
|View full text |Cite
|
Sign up to set email alerts
|

From Menarche to Menopause: Trends among US Women Born from 1912 to 1969

Abstract: The authors investigated secular trends in age at menarche, age at menopause, and reproductive life span within a population-based cohort of US women. Study subjects were 22,774 women selected randomly as controls for a case-control study. Eligible controls were residents of Wisconsin, Massachusetts, or New Hampshire born between 1910 and 1969. Subjects completed telephone interviews in 1988-2001 and answered questions regarding reproductive and lifestyle factors. Birth cohorts were created using 5- and 10-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
139
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(157 citation statements)
references
References 55 publications
14
139
1
3
Order By: Relevance
“…This median age at menopause appeared to be within the ranges which were observed in the western countries [6]. In a population-based cohort of over 22 000 women from three regions of the US, the median age of natural menopause was found to be 50.5 years [7]. A review article which was written by Palacios et al showed that the median age at menopause in Europe ranged from 50.1 to 52.8 years, that in north America, it ranged from 50.5 to 51.4 years, that in Latin America, it ranged from 43.8 to 53 years, and that in Asia, it ranged from 42.1 to 49.5 years [8].…”
Section: Discussionsupporting
confidence: 55%
“…This median age at menopause appeared to be within the ranges which were observed in the western countries [6]. In a population-based cohort of over 22 000 women from three regions of the US, the median age of natural menopause was found to be 50.5 years [7]. A review article which was written by Palacios et al showed that the median age at menopause in Europe ranged from 50.1 to 52.8 years, that in north America, it ranged from 50.5 to 51.4 years, that in Latin America, it ranged from 43.8 to 53 years, and that in Asia, it ranged from 42.1 to 49.5 years [8].…”
Section: Discussionsupporting
confidence: 55%
“…Other factors such as the average increase in the number of reproductive years reported in women in the United States (80) and in Hong Kong (68) may have played a role in the trend breaks observed in women, but would not explain parallel changes in hip fractures in men. Other contributors, such as smoking cessation, (90) improvement in physical activity, (91) calcium intake and vitamin D status, (25,92) and fall prevention, (68,93,94) could have also influenced, to a limited extent, the hip fracture rates.…”
Section: Discussionmentioning
confidence: 96%
“…(79,80) Increased urbanization could also reflect an associated increase in prosperity and access to medical care, which could, theoretically, increase survival of the frailest elderly, as was recently proposed as a possible contributor to the increase in fracture rates among older Korean women. (81) Of equal interest are the declining rates of fractures now being observed in North America, Europe, Hong Kong, and Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…As the polymorphism may be in linkage disequilibrium with another allele, an alternative locus may be the true functional polymorphism. Previous studies have indicated that there is a major haplotype of the human MDM4 (14,15). This haplotype is tagged by several SNPs, which are in high linkage disequilibrium, across the MDM4 gene, including the polymorphic locus rs1563828.…”
Section: Discussionmentioning
confidence: 99%